Emotion by design creative leadership lessons from a life at Nike - Hoffman, Greg. (London Cornerstone Press, 2022)
In EMOTION BY DESIGN, Nike's former CMO shares lessons and stories from three decades within the company. Readers will learn how Nike continues to not just expand its reach but deepen its bonds through groundbreaking, savvy messaging that's authentic as well. The lesson that he'll return to over and over again is that everything stems from ideas. The only limitations on those ideas come from the limitations an organization places on itself, in terms of personnel, in terms of freedom to experiment, and in terms of numbers. Unfortunately, in the age of big data, the numbers, Hoffman argues, are too often getting in the way. Hoffman came to Nike at a tipping point in the brand's growth, when a domestic sports apparel company was about to become a global cultural juggernaut. At the beginning he was a student of Nike's culture, its maxims and best practices, but eventually he found a way to bring his own unique perspective into the boardroom. That perspective was one distinguished by both his race - as one of the few Black faces at the table-and his background as a student of fine art. Over the course of a twenty-seven year career-from intern to Chief Marketing Officer-Hoffman had a hand in crafting Nike's singular brand and was instrumental in some of its most high profile campaigns. For Hoffman, art and sport and commerce all needed to combine for the messaging around every product. Every campaign was different and yet the result was the same: an emotional bond between products and people. No brand does that as successfully as Nike, and Hoffman is here to show you how"
Includes bibliographical references and index.
Keywords: Nike (Firm) | Sporting goods industry--United States. | Creative ability in business. | Leadership. | Marketing--Psychological aspects. | Advertising--Psychological aspects